Influence of Bagasse/Sisal Fibre Stacking Sequence on the Mechanical Characteristics of Hybrid-Epoxy Composites - Jafrey Daniel James D; S. Manoharan; G. Saikrishnan; S. Arjun (Journal of Natural Fibers, 2020)
The current study deals with the mechanical and morphological properties of sisal/bagasse fibers reinforced epoxy composites. The composites were developed by the hand layup process in four different proportions of sisal/bagasse fibers. The produced composites were characterized for its mechanical characteristics, namely, tensile, flexural, impact, Shore D hardness compression tests, water absorption and biodegradation tests as per ASTM. Morphologies were studied using Scanning Electron Microscopy. It was inferred that composites with three layers of sisal fibers and a core layer of sisal fibers produced good properties.